Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »–Page 4 de la couverture.
Section: ix, 306 pages ; 24 cm.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

The Logic of masculinist protection: Reflections on the current security state - Young, Iris Marion (Signs, 2003)
Keywords: amériques; approches et analyses; discipline; discours dominant; histoire et politique; masculinité; patriarcat; philosophie; philosophie politique; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; sécurité nationale; thématiques; états-unis